PERBANDINGAN KURIKULUM PENDIDIKAN DASAR DAN MENENGAH DI INDONESIA DITINJAU DARI SEGI DESAIN, METODOLOGIS, DAN EVALUASI, 1968–2006 (Jurnal Teknodik, 2019)
This qualitative descriptive research was trying to find the basic differences of national curriculum of primary and secondary school in Indonesia since 1968 until 2006. It was a library research, and conducted on September 2007 in Jakarta. The observed differences were curriculum design, methodological approach, and evaluation. One of factors of curriculum change was the differences of angle to see the education itself. The differences of curriculum design and methodological approach were structure of contents and the ways to implement the instructional in classes. Meanwhile, the differences of evaluation were the existence of instrument of evaluation and the way to evaluate the student’s instructional process and results.